2018
DOI: 10.12973/iji.2018.11432a
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Supervision, Teachers’ Attitude towards Classroom Supervision and Students’ Participation

Abstract: This quantitative study aims to identify the supervisory performance in the elements of teaching and learning supervision in secondary schools in the Kubang Pasu district, Kedah. Theory of classroom teaching and learning supervision by Glickman (2004) is the basis of the study. Research instruments are adapted and modified from teaching and learning supervision by Ebmeir (2003), while teacher's attitude towards supervision was taken from the questionnaire by Ramin (2014) and teacher's teaching competency instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…This dimension consists of 12 valid items with a reliability level of 0.96. Several research results showed that supervisors' support for the teaching and learning processes has a significant relationship with teachers' attitudes towards supervisors (Daud et al, 2018;Khumaedi, 2012;Ryan & Gottfried, 2012). It was further stated by Kazi, et al, (Hoque et al, 2020) that in an effort to improve the quality of teaching, supervision can be used as a strategy that allows teachers to achieve high quality learning goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dimension consists of 12 valid items with a reliability level of 0.96. Several research results showed that supervisors' support for the teaching and learning processes has a significant relationship with teachers' attitudes towards supervisors (Daud et al, 2018;Khumaedi, 2012;Ryan & Gottfried, 2012). It was further stated by Kazi, et al, (Hoque et al, 2020) that in an effort to improve the quality of teaching, supervision can be used as a strategy that allows teachers to achieve high quality learning goals.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment dimension encompasses a set of assessments on the implementation of teaching and learning processes by teachers (Directorate General of Teachers and Education Personnel, 2016). The supervision for school principals and teachers in assessing the learning process is an important thing that must be performed continuously and consistently to make professional teachers (Ajasan et al, 2016;Daud et al, 2018;Khun-Inkeeree et al, 2019 ). To find out the teachers' attitudes towards the dimension of assessment, 15 validated items were developed and resulted with a reliability level of 0.97.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This partnership exists because teachers are committed to and trust their teaching and learning supervisors. Teachers are also pleased with school leadership, as supervisors use a variety of communication strategies, have fair supervision decisions, have comprehensive knowledge of successful teaching techniques [43]. Their supervisors also have a background in supervisory techniques and supervisors are also able to improve the standard of teaching in the classroom and are in line with the elements described in [29] questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, studies affirm that the quality of education to some extent depends on the quality and quantity of supervision support offered to teachers in schools (De Grauwe & Carron, 2011a;UNESCO, 2015b). Furthermore, supervisory support to teachers has the potential to improve classroom practices by improving the quality of teachers' teaching skills, leading to student success by way of improving teachers' professional growth and work performance (Baffour, 2011;Daud et. al., 2018;Kholid & Rohmatika, 2019;Mofareh, 2011;Mukoro & Pupu, 2013;Pajak, 2001).…”
Section: Introductionmentioning
confidence: 99%